Zachariah Mcelhoes: capstone - Mcelhoes, Zachariah, artist (Colorado State University. Libraries, 2015)
The artist's statement: As a graphic designer my goal is to make beautiful market oriented designs that enhance the products they adorn and endorse. I am a firm believer that rules are meant to be broken and have sought to push the limits of graphic design through use of different mediums. Utilizing alternative production methods have also been a tool in which I have tried to push my comfort level with design. I have always admired work that makes people stop and look further at the product it accompanies or at the design itself. This is the goal I have strived for in my own work; I want people to stop and examine and wonder about my work. I incorporate both typographical elements into my work as well as illustrative elements in order for a design to be realized to its fullest potential. Some of the unique ways that I try to push my work is by utilizing digital fabrication production techniques. CNC milling machines, vinyl cutters, and lazar engravers are the main machines that I have utilized during my undergraduate career. I have used these machines as tools to accomplish a graphical design that would have been imposable with tradition graphic design methods. Good clean designing is essential for my designs to succeed and I will often whittle a design down to its bar bones decided what is essential to communicate the essential message and then build it back up. I am an extremely hard work but having fun is an essential part of how I am and I try not to take myself too seriously. Both of these elements can be seen in my work with playful but precise elements incorporated into them. I always like my work to speak louder than my own words so I hope you enjoyed or enjoying look at it.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.